TOPICAL USE OF CALCINEURIN INHIBITORS FOR DISCOID LUPUS ERYTHEMATOSUS-A SYSTEMATIC REVIEW (The Research of Medical Science Review, 2024)
Background: Discoid lupus erythematosus is a persistent skin condition marked by inflammatory plaques. Without timely diagnosis and intervention, it can result in scarring and skin atrophy, potentially causing disfigurement. The primary treatment for DLE involves the use of topical steroids i.e. calcineurin inhibitors. Objectives: The objective of this review is to assess the topical use of calcineurin inhibitors for Discoid Lupus Erythematosus. Methodology: The included studies fell into various categories, including published peer-reviewed articles, clinical trials, observational studies, case-control studies, and case reports. After comprehensive review, eleven articles met the inclusion criteria and included in this review. Results: Mostly patients with DLE have lesions on face and scalp. Majority of studies used topical tacrolimus with different concentrations while other used pimecrolimus. Conclusion: Calcineurin inhibitors have a suitable effect for treating DLE. They are used as a maintenance therapy to treat chronic or recurring DLE lesions, aiding in the long-term control of the condition.